Nutritional and therapeutic potential of functional components of brown seaweed: A review - Yuliya V. Alloyarova; Daria S. Kolotova; Svetlana R. Derkach (Foods and Raw Materials, 2024)
Seaweed has a unique chemical composition with an abundance of bioactive substances. In Russia, brown seaweed grows in the coastal areas of the Pacific Ocean (Far East) and the seas of the Arctic Ocean. This review focuses on the therapeutic and nutritional potential of functional components of brown seaweed. It was based on a systematic analysis of research and review articles published from 2010 to 2023 and indexed in Scopus, Web of Science, and eLIBRARY.RU. Our particular interest was in seaweed’s bioactive components such as polysaccharides, phenolic compounds, vitamins, lipids and fatty acids, proteins, peptides, and amino acids. Compounds extracted from brown seaweed exhibit antioxidant, antiglycemic, antitumoral, neuroprotective, anti-inflammatory, anticoagulant, antibacterial, and immunostimulating properties. Brown seaweed and its derivatives are used as structural modifiers, antioxidants, preservatives, moisture-retaining agents, and sources of vitamins and minerals in the development of functional and preventive food products. They are also used as ingredients in meat, dairy, bakery and flour products, as well as in food additives and beverages, to provide potential health benefits and essential nutrients. Studies have proven the functional effectiveness of food products containing brown seaweed and its derivatives. The incorporation of seaweed components into functional foods could contribute to global food security. More research is needed to develop new competitive products based on seaweed and to investigate them for the presence of substances hazardous to humans and the environment.